Establishment of Reference Value of 20 Amino Acids for Toddlers by High Performance Liquid Chromatography Tandem Mass Spectrometry - Pasaribu, Merci Monica br; Immanuel, Suzanna; Sjarif, Damayanti Rusli; Timan, Ina Susianti; Malik, Safarina G.; Mansyur, Muchtaruddin; Simanjuntak, Ernawati (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Amino acids are one of the essential metabolites, especially the 20 amino acids that are preserved as the building blocks of protein. Alterations in amino acid concentrations are related to disease such as inborn error of metabolism, cancer, as well as nutritional status. Hence, it is necessary to define reference values of 20 plasma-free amino acids for Indonesian toddlers and to establish a robust measurement technique using chromatography with tandem mass spectrometry (MS).METHODS: This study was a cross-sectional preliminary study to establish reference values. The sample was prepared by mixing plasma with 20% sulfosalicylic acid. Plasma-free amino acids were measured with high-performance liquid chromatography (HPLC) non-derivatization technique using column XTerra for chromatographic separation coupled with tandem MS. Amino acids reference values were taken from 101 healthy Indonesian toddlers aged 1-3 years old. Since amino acids data were not Gaussian distributed, the lower and upper of the reference value was established from the 5th percentile and the 95th percentile, respectively.RESULTS: Analysis for 20 amino acids was validated. The accuracy ranged from 90.53-105.39% and the precision ranged from 0.06-3.80%. The limit of detection range was 1-2 nmol/mL, and the limit of quantification range was 2-4 nmol/mL. The result was linear, with R2 higher than 0.998. There was no significant difference between boys and girls for all amino acids except for glycine.CONCLUSION: HPLC with tandem MS method can be used to evaluate amino acids in clinical practice. The reference values obtained are specific for aged 1-3 years old from urban areas in Indonesia. The study suggests that for each population, the reference values for amino acids should be established.KEYWORDS: amino acids, high-performance liquid chromatography, tandem mass spectrometry, reference values, Indonesia